PENGARUH LATIHAN ONE LEG JUMP DAN LATERAL JUMP OVER BARRIER TERHADAP POWER OTOT TUNGKAI KEMAMPUAN SMASH BOLA VOLI - Abrian, Akhmad Rizal (Universitas Negeri Semarang, 2021)
Leg muscle strength can be improved with plyometric exercises such as One Leg Jump and Lateral JumpOver Barrier. This study aims to determine the effect of One Leg Jump and Lateral Jump Over BarrierExercises on the Power of Limb Muscle Smash Ability. This research is an experimental research. The sampleof this study found 20 people. The ndependent variables are One Leg Jump and Lateral Jump Over Barrierpluometric axercises. And based on the variable, namely the Power of the Leg muscles of the Male VolleyballPlayer Sakalima. The research is to tesy hypothesis 1 the effect of One Leg Jump and Lateral Jump OverBarrier Exercises on the Muscle Power of the Legs of The volleyball players of the Sakalia Club Tegal in2021. This is the result of the -t-test. What was done was showing a significance value of 0.000, the valuewas less than the specified significence lavel of 5% (0.05). in the addition, there is also a difference in theaverage (mean) between the initial test san the final teas which shows an increase or change.the conclusionof the study is that One Leg Jump and Lateral Jump Over Barrier exercises on Leg Muscle Power have thesame effect on leg muscle power training. However, the Lateral Jump Over Barrier exercise is more influentialthan the One Leg Jump on leg muscle power. Adcice Exercise One Leg Jump and Lteral Jump Over Barrieris batter done in a balanced again in order to get maximum results.